Economic Sector Potential Analysis of Kutai Kartanegara and Penajam Paser Utara Regencies in East Kalimantan as Indonesia's New Capital City 2045 - Saputri, Miska Pudhenta Nuke; Udjianto, Didit Welly; Wijayanti, Diah Lufti (International Journal of Tourism and Hospitality in Asia Pasific, 2024)
In an effort to realize equal development and economic growth, the government plans to move the center of Indonesia's government from Jakarta to East Kalimantan. The new name of the capital city is the National Capital City (IKN) of the Archipelago. The IKN development megaproject is expected to take around 15-20 years. To develop the existing potential in Kutai Kartanegara and Penajam Paser Utara, regional development planning and economic potential measurement are needed. The purpose of this research is to find and analyze the leading sectors. The leading sector and the description of regional economic sectors can be identified through 1). Location Quotient (LQ) analysis, used to determine the base and non-base sectors in the economy; 2).Shift Share analysis, used to determine changes and shifts in economic structure. This research uses secondary data in the form of time series of Gross Regional Domestic Product (GRDP) of Kutai Kartanegara and Penajam Paser Utara Regencies in 2013-2022. From the results of the analysis, it is concluded that in Kutai Kartanegara Regency there are 3 basic sectors and 14 non-basic sectors, while in North Penajam Paser Regency there are 10 basic sectors and 7 non-basic sectors. From the results of the Shift Share analysis, it is known that the economic sectors in Kutai Kartanegara Regency are superior, prospective, and mainstay sectors. Meanwhile, in Penajam Paser Utara Regency, the leading, prospective, mainstay, and lagging sectors.